KRISTOLOGI OA MATA MUSAN: Kajian Kristologi dalam Budaya Tetun - Jeni Isak Lele; Santriana A. Luruk; Yanti E. Sole; Ezra Tari (Misioner, 2021)
The understanding of Christ in local customs and culture is still very minimal. Christ has been known only from the western face. Discussions around the nature of Jesus as God or man. There are several writings on Christology in culture, for example, wayang in Javanese culture. Papuan also knew Jesus is known as the Reconciler. In Toraja, Jesus is known as Pangala Tondok. So the author wants to offer one of the Christologies in the Tetun culture. This research explores the Belu people's lives, especially in performing the oa mata musan ritual. This paper does not address the theological debate about the nature of Jesus. However, this study discusses how local people can understand Jesus in their existence. The research method used by the author is phenomenology. Phenomenology is used as a tool to understand facts in the field. This paper contains an offer to the Belu people regarding how they know Christology through their custom. They can realise Christ incarnate in the form of Oa Mata Musan. Oa Mata Musan as a mediator or mediator for conflicting families. Thus Jesus is present as a peacemaker.